Assessment of the acute and subacute toxicity of the aqueous extract of Moroccan Ferula communis fruit in a mouse model - Ghizlane Nouioura; Meryem Tourabi; Adel Tahraoui; Karima El-yagoubi; Souad Maache; Hinde Elfatemi; Badiaa Lyoussi; El houssine Derwich (Elsevier, 2023)
Ferula communis L. is thought to possess a wide range of therapeutic qualities. This plant's safety is critical regarding its potential uses as a medicine. Using the techniques outlined in the OECD recommendations, the present study aimed to assess the acute and subacute toxicity profiles of Ferula communis aqueous extract (FC-Ext) in mice. In the acute study, the FC-Ext was administered to adult male and female Swiss albino mice through oral and intraperitoneal routes at doses of 0-4 g/kg. The general behavioral effects, mortality rates, and latency of mortality were evaluated for a period of 14 days. For the sub-acute dose study, the FC-Ext was administered orally to adult mice at doses of 125, 250, and 500 mg/kg on a daily basis for 28 days. Body weight and selected biochemical and hematological parameters were measured, and histological examinations of the liver, kidney, and spleen were conducted to assess any signs of organ damage at the end of the treatment period. The results of the acute toxicity study demonstrated that the LD50 values for the oral and intraperitoneal administration of FC-Ext were 3.6 g/kg and 2.3 g/kg, respectively. In the subacute toxicity study of FC-Ext, no significant changes in body weight were observed. However, a substantial increase in the weights of the liver, kidney, and spleen was observed in male mice. The administration of FC-Ext to mice at doses higher than 250 mg/kg resulted in a decrease in white blood cells and platelets in both sexes and a reduction in red blood cells and mean corpuscular hemoglobin concentration in males and hemoglobin in females. No changes in biochemical parameters were observed. Microscopic examination of vital organs such as the liver, kidney, and spleen revealed no significant injuries. Based on the current results, the aqueous extract of Ferula communis has low toxicity. These findings provide important information about the toxicity profile of the traditional medicine plant Ferula communis.